From QTL to variety-harnessing the benefits of QTLs for drought, flood and salt tolerance in mega rice varieties of India through a multi-institutional network. (January 2016) - Singh, Renu; Singh, Yashi; Xalaxo, Suchit; Verulkar, S.; Yadav, Neera; Singh, Shweta; Singh, Nisha; Prasad, K.S.N.; Kondayya, K.; Rao, P.V. Ramana; Rani, M. Girija; Anuradha, T.; et al.
Highlights: Marker-assisted backcross improvement of mega varieties of rice. QTLs for drought, submergence and salt tolerance. Foreground and recombinant selection. Background selection using high density 50K SNP chip. Abstract: Rice is a staple cereal of India cultivated in about 43.5 Mha area but with relatively low average productivity. Abiotic factors like drought, flood and salinity affect rice production adversely in more than 50% of this area. Breeding rice varieties with inbuilt tolerance to these stresses offers an economically viable and sustainable option to improve rice productivity. Availability of high quality reference genome sequence of rice, knowledge of exact position of genes/QTLs governing tolerance to abiotic stresses and availability of DNA markers linked to these traits has opened up opportunities for breeders to transfer the favorable alleles into widely grown rice varieties through marker-assisted backcross breeding (MABB). A large multi-institutional project, "From QTL to variety: marker-assisted breeding of abiotic stress tolerant rice varieties with major QTLs for drought, submergence and salt tolerance" was initiated in 2010 with funding support from Department of Biotechnology, Government of India, in collaboration with International Rice Research Institute, Philippines. The main focus of this project is to improve rice productivity in the fragile ecosystems of eastern, northeastern and southern part of the country, which bear the brunt of one or the other abiotic stresses frequently. Seven consistent QTLs for grain yield under drought, namely, q DTY1.1, q DTY2.1, q DTY2.2, q DTY3.1, q DTY3.2, qDTY 9.1 and q DTY12.1 are being transferred into submergence tolerant versions of three high yielding mega rice varieties, Swarna-Sub1, Samba Mahsuri-Sub1 and IR 64-Sub1. To address the problem of complete submergence due to flash floods in the major river basins, the Sub1 gene is being transferred into ten highly popular locally adapted rice varieties namely, ADT 39, ADT 46, Bahadur, HUR 105, MTU 1075, Pooja, Pratikshya, Rajendra Mahsuri, Ranjit, and Sarjoo 52. Further, to address the problem of soil salinity, Saltol, a major QTL for salt tolerance is being transferred into seven popular locally adapted rice varieties, namely, ADT 45, CR 1009, Gayatri, MTU 1010, PR 114, Pusa 44 and Sarjoo 52. Genotypic background selection is being done after BC2 F2 stage using an in-house designed 50K SNP chip on a set of twenty lines for each combination, identified with phenotypic similarity in the field to the recipient parent. Near-isogenic lines with more than 90% similarity to the recipient parent are now in advanced generation field trials. These climate smart varieties are expected to improve rice productivity in the adverse ecologies and contribute to the farmer's livelihood.